Edukasi Keuangan Pelajar: Peningkatan Literasi Keuangan dan Pengenalan Investasi pada Generasi Z untuk Mencapai Tujuan Keuangan Berkelanjutan - Fathihani Fathihani; Vely Randyantini; Ika Puji Saputri; Dewi Sri Handayani; Doni Kusuma (Pusat Riset dan Inovasi Nasional, 2026)
Generation Z is a productive demographic that has grown up in the digital era and is accustomed to the ease of digital financial transactions. However, their level of financial literacy remains relatively low. Data from the National Survey of Financial Literacy and Inclusion (OJK, 2022) shows that Indonesia’s financial literacy rate has only reached 49.68%. Limited financial management skills and a tendency toward consumptive behavior further contribute to Generation Z’s lack of understanding of proper financial management practices. This Community Service Programme (PkM) aims to improve young people’s comprehension of fundamental financial literacy concepts, financial planning, and the introduction of legal, needs-based investment, particularly among vocational high school students. The training guides participants in managing income, preparing budgets, distinguishing between needs and wants, and understanding investment instruments such as mutual funds and stocks. The PkM implementation consists of several stages, including an initial assessment of participants’ financial literacy, interactive training through lectures, quizzes, and group discussions, mentoring in developing personal financial plans, and outcome evaluation using pre-tests and post-tests. Evaluation results demonstrate a clear improvement in participants’ understanding of financial literacy and investment concepts. These findings indicate that interactive and application-based training methods are effective in increasing financial knowledge and awareness. Overall, the programme successfully achieved its objectives and positively influenced students’ financial knowledge and attitudes.